Integrasi-interkoneksi Sains Islam pada Mata Kuliah Antropobiologi - Irma Dwi Tantri; Malia Fransisca; Ahmad Bagus Romadhon; Latif Alahmasi (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
Islamic Higher Education (PTAI) is expected to be a research based university with international competitiveness without losing its characteristics. It is necessary to eliminate the scientific dichotomy by integrating science with Islamic religious studies. At IAIN Purwokerto, the concept of integration-interconnection is manifested in “Jabalul Hikmah”. The epistemological reintegration of the scientific foundations is expected to answer academic, religious, social, cultural, and technological problems in society. One of the subjects based on general science which needs to be integrated with Islamic studies is Anthropobiology. Hence, this study aims to examine how to present anthropobiology courses in an integrated interconnected with Islamic studies. This research is a library research conducted by collecting and analyzing data from books, journals, and articles related to scientific integration models and anthropobiological concepts in pure science and Islamic perspectives. In the Miles and Huberman model, the collected will be reduced to focus on the important things, then the data is presented, and finally verified. The results show that efforts to integrate Islamic science in Anthropobiology course material can be done by integrating anthropobiological concepts derived from universal truths with Islamic studies. Through the integration-interconnection of Islamic science, Anthropobiology courses can support Islamic Early Childhood Education Study Program students to have a comprehensive understanding of human characteristics to prepare early childhood education.